Determinants of acquisition and failure: stylized facts and lessons for empirical studies - Jens Köke (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2001)
This study provides new stylized facts on the determinants of corporate failure and acquisition in Germany. It also offers important lessons for the design of empirical studies. We show that firms experiencing failure or acquisition are significantly different from surviving firms on a number of firm-specific characteristics, however the characteristics are similar for failing and acquired firms. This implies that firm failure and acquisition should be analyzed in combination. Second, we find that the industry distribution is significantly different for failure and acquisitions. This calls for some kind of industry-adjustment in empirical analyses. Third, the differences between surviving and failing (acquired) firms are similar, irrespective whether the respective firm characteristic is observed one or up to four or more years before failure (acquisition). This validates the findings of studies that use lags of only one year for explanatory variables.
Keywords: G34; G33; G32; 330; Corporate governance; ownership structure; bankruptcy; acquisitions; Konkurs; Übernahme; Betriebsvergleich; Corporate Governance; Eigentümerstruktur; Branche; Kapitalstruktur; Reorganisation; Deutschland